2019
DOI: 10.2196/12656
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of User Segmentation for Designing Digital Therapy for Adolescent Mental Health: Findings From Scoping Processes

Abstract: BackgroundNew Zealand youth, especially those of Māori and Pacific descent, have high rates of depression, anxiety, and self-harm, but have low rates of help-seeking from mental health professionals. Apps, computerized therapy, and other digital tools can be effective, highly scalable treatments for anxiety and depression. Co-design processes are often used to foster engagement with end users, but this does not always lead to high levels of engagement.ObjectiveWe aimed to carry out preliminary scoping to under… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 25 publications
7
82
0
Order By: Relevance
“…The lack of engagement with individual mental health apps, with recent data suggesting a 4% daily open rate (Baumel et al, 2019), highlights the challenges for even those apps featured highly on the commercial marketplaces. Reasons for the lack of engagement with these apps vary but include a lack of customisation (Fleming et al, 2019), skepticism of efficacy (Muse and Topol, 2019), concerns around privacy (Huckvale et al, 2019), challenges around usability (Sarkar et al, 2016), incompatibility with older or cheaper phones and lack of actionability (Torous et al, 2018). There are thousands of apps that offer functions such as mood tracking or mindfulnessbut those numbers decay to single digits when looking for safe, evidencebased and adaptable tools.…”
mentioning
confidence: 99%
“…The lack of engagement with individual mental health apps, with recent data suggesting a 4% daily open rate (Baumel et al, 2019), highlights the challenges for even those apps featured highly on the commercial marketplaces. Reasons for the lack of engagement with these apps vary but include a lack of customisation (Fleming et al, 2019), skepticism of efficacy (Muse and Topol, 2019), concerns around privacy (Huckvale et al, 2019), challenges around usability (Sarkar et al, 2016), incompatibility with older or cheaper phones and lack of actionability (Torous et al, 2018). There are thousands of apps that offer functions such as mood tracking or mindfulnessbut those numbers decay to single digits when looking for safe, evidencebased and adaptable tools.…”
mentioning
confidence: 99%
“…However, implementing face-to-face CBT in programs for youth offenders is challenging due to a shortage of therapists with the requisite skills. Computerized CBT (cCBT) has been shown to be effective and acceptable in adolescent populations (Ebert et al, 2015;Christensen et al, 2011;Merry et al, 2012), and could increase access to therapy among hard-to-reach groups (Fleming et al, 2019a). However, few cCBT programs for adolescents have been trialled outside of school or health care settings, and we found just one published trial of cCBT among youth offenders (Wannachaiyakul et al, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…Gulliver, Griffiths, and Christensen (33) reviewed qualitative and quantitative studies, and found that adolescents identified the most significant barriers to help-seeking as: perceived stigma and embarrassment, difficulty recognizing symptoms (i.e., poor mental health literacy), and a preference for self-reliance. We have previously identified that even looking up a website "for depression" in private can be off putting for some adolescents (34). Computerized approaches that avoid the terminology linked to diagnostic categories may help to reduce the barriers associated with stigma and embarrassment, whether a young person is seeking help via a professional or on their own (e.g.…”
Section: Discussionmentioning
confidence: 99%